Mechanical properties and water resistance of alkali-activated flood-control stone incorporating ball-milling treated Yellow River silt - Yingbin Song; Xiangping Zhang; Jinxia Xu; Sheng Jiang; Zhong Yanhui (Case Studies in Construction Materials)
The low pozzolanic activity of the silt in the Yellow River has always been the key factor that hinders its resource utilization as artificial stones. A high-speed ball-milling method was first attempted to pretreat the silt for enhancing its pozzolanic activity in this study. The artificial stones incorporating the ball-milled silt were prepared by the alkali-activation method. The changes in the basic physical and chemical properties and microstructures of the pre-treated silt and fabricated artificial stones were characterized. Also, the compressive strength, splitting tensile strength and water resistance of fabricated specimens were measured. The results show that the ball-milling treatment destroys the original crystal structure, and significantly enhances the potential pozzolanic activity of the silt. In addition, it improves the compressive strength, splitting tensile strength and water resistance of the artificial stones. The compressive strength of artificial stones incorporated with the ball-milled silt has a maximum value of 17.1 MPa, showing an increase by one time. It can be ascribed to the increase of C-S-H/C-A-S-H gel amount in specimens. Furthermore, compared to traditional mined bluestone, the carbon emission of the alkali-activated artificial stone incorporating ball-milled Yellow River silt is much lower. The production of 1 t of artificial stone only emits 1155.25 kg of CO2.